PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI DALAM MENINGKATKAN KINERJA PEGAWAI DI KANTOR CAMAT WOHA PADA TAHUN 2024 - Suci Mulyati; Putri Rahyu; Nuryadin (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2025)
Study with the title of the influence of leadership and organizational culture in improving performance at the Woha sub-district office, this study intends to determine the improvement of employee performance at the Woha sub-district office in 2024, the findings in this study reveal that leadership has an effect on improving employee performance at the Woha sub-district office and organizational culture is also able to improve employee performance at the Woha sub-district office. This study utilizes 2 (two) variables, namely leadership and organizational culture concluded by simultaneous and partial methods which conclude that from various tests carried out on the Classical Assumption Test table, namely the findings of the Normality Test, Autocorrelation Test (Model Summaryb), Linearity Test (ANOVA Table), and Hypothesis Test, namely Partial Test (t Test), f Test (Simultaneous Test) ANOVAb, Determination Test (R2) Model Summary. Thus, using the SPSS application for Windows Version 21, multiple linear regression tests were carried out. An equation for multiple linear regression is produced Employee Performance = 3,341 + 3.489 Leadership - 1,954 Culture + e. Keywords: Employee Performance, Leadership and Organizational Culture